MATH SOLVE

3 months ago

Q:
# HELP ASAP!!!!!! 20 Points and will mark brainliest for correct answer!

Accepted Solution

A:

6x^2 - 2x = 7

6x^2 - 2x - 7 = 0

[tex] x = \dfrac{-b \pm \sqrt{b^2 - 4ac}}{2a} [/tex]

[tex] x = \dfrac{-(-2) \pm \sqrt{(-2)^2 - 4(6)(-7)}}{2(6)} [/tex]

[tex] x = \dfrac{2 \pm \sqrt{4 + 168}}{12} [/tex]

[tex] x = \dfrac{2 \pm \sqrt{172}}{12} [/tex]

[tex] x = \dfrac{2 \pm 2\sqrt{43}}{12} [/tex]

[tex] x = \dfrac{1 \pm \sqrt{43}}{6} [/tex]

6x^2 - 2x - 7 = 0

[tex] x = \dfrac{-b \pm \sqrt{b^2 - 4ac}}{2a} [/tex]

[tex] x = \dfrac{-(-2) \pm \sqrt{(-2)^2 - 4(6)(-7)}}{2(6)} [/tex]

[tex] x = \dfrac{2 \pm \sqrt{4 + 168}}{12} [/tex]

[tex] x = \dfrac{2 \pm \sqrt{172}}{12} [/tex]

[tex] x = \dfrac{2 \pm 2\sqrt{43}}{12} [/tex]

[tex] x = \dfrac{1 \pm \sqrt{43}}{6} [/tex]